Effect of length of storage on reconstituted sorghum grain silages treated with sodium benzoate on nutritive value and dairy cow performance - Santos, Willian Pereira dos (2019)
Ensiling high moisture grain often increases starch and protein digestibilities due proteolysis during storage. However, the length of storage is fundamental to allow great protein matrix break down. The central objective of this work was to evaluate the effect of length of storage of reconstituted sorghum grain silage (RSGS) on dairy cows performance. Simultaneously it was evaluated the effect of sodium benzoate on silage nutritive value and its impact on animal performance. The hypothesis was that sodium benzoate reduces proteolitic activity due its antimicrobial properties. Two sequential experiments with mid-lactation Holstein dairy cows were set. The first experiment evaluated the effect of different length of storages on RSGS treated or not with sodium benzoate (0.2% as fed). Silages treated with additive (Benzoate) and non-treated (Control) were stored for 30 or 90 days prior feeding. Twenty mid-lactation dairy cows with 168 ± 87 days in milk (DIM) were used in 5 replicated 4 × 4 Latin square design with a 2 × 2 factorial arrangement. Dry ground sorghum grain was reconstituted to 35% moisture and ensiled in 200-L plastic drums. Treatments were: RSGS stored for 30 days without additive (30 CON), RSGS stored for 30 days with sodium benzoate (30 BEN), RSGS stored for 90 days without additive (90 CON) and RSGS stored for 90 days with sodium benzoate (90 BEN). Lengthening silage storage increased 1,2-propanediol concentration and protein solubility of silages. Milk yield was greater in favor of cows fed silage stored for 90 days compared to 30 days (31.2 vs. 30.0 kg/d). Starch (89.3 vs. 86.9%) and protein (57.1 vs. 54.0%) digestibility was also greater for silages stored for 90 days compared to 30 days. Sodium benzoate reduced silage ethanol concentration (0.20 vs. 0.08% of DM), but did not altered statistically protein solubility (CON = 18.9 vs. BEN = 15.6% of CP) or ammonium-N (CON = 4.38 vs. BEN = 3.94 % of N). The second trial were conducted with 12 mid-lactation dairy cows (170 ± 47 DIM) to evaluated the effect of sodium benzoate on nutritive value and dairy cows performance fed RSGS stored for 150 days, treated (Benzoate) or not (Control) with sodium benzoate. Cows received a standard diet containing dry ground sorghum for 14 days. At the end of adaptation period, cows were paired blocked and randomly assigned to one of two treatments (Control or Benzoate) for 28 experimental days. During experimental period cows received the same diet with the exception of dry ground sorghum, which was totally replaced with RSGS. Silages treated with sodium benzoate had low ethanol (0.84 vs. 0.18 % of DM) and ethyl-lactate (388 vs. 157 mg/kg of DM) concentration as a consequence of low yeast population (4.73 vs. 2.52 log cfu/g). Soluble protein was reduced on treated silages (26.2 vs. 20.6 % of CP). Aerobic stability was higher for treated silages (51 vs. 146 h). Dairy cow performance was not altered by treating silages with sodium benzoate. In conclusion, extending the length of storage of RSGS increased dairy cows use feed efficient and nitrogen use efficiency due higher starch and protein digestibility. Sodium benzoate promoted typical response on silage fermentation and did not alter animal performance.